Evaluation of Antileishmanial Activity of Selected Brazilian Plants and Identification of the Active Principles. (9th June 2013) - Filho, Valdir Cechinel; Meyre-Silva, Christiane; Niero, Rivaldo; Bolda Mariano, Luisa Nathália; Gomes do Nascimento, Fabiana; Vicente Farias, Ingrid; Gazoni, Vanessa Fátima; dos Santos Silva, Bruna; Giménez, Alberto; Gutierrez-Yapu, David; Salamanca, Efrain; Malheiros, Angela
Abstract : This study evaluated extracts, fractions, and isolated compounds from some selected Brazilian medicinal plants against strains of promastigotes of Leishmania amazonensis and L. brasiliensis in vitro . The cell viability was determined, comparing the results with reference standards. The dichloromethane fractions of the roots, stems, and leaves of Allamanda schottii showed IC50 values between 14.0 and 2.0 μ g/mL. Plumericin was the main active compound, with IC50 of 0.3 and 0.04 μ g/mL against the two species of Leishmania analyzed. The hexane extract of Eugenia umbelliflora fruits showed IC50 of 14.3 and 5.7 μ g/mL against L. amazonensis and L. brasiliensis, respectively. The methanolic extracts of the seeds of Garcinia achachairu and guttiferone A presented IC50 values of 35.9 and 10.4 μ g/mL, against L. amazonensis, respectively. The ethanolic extracts of the stem barks of Rapanea ferruginea and the isolated compound, myrsinoic acid B, presented activity against L. brasiliensis with IC50 of 24.1 and 6.1 μ g/mL. Chloroform fraction of Solanum sisymbriifolium exhibited IC50 of 33.8 and 20.5 μ g/mL, and cilistol A was the main active principle, with IC50 of 6.6 and 3.1 μ g/mL against L. amazonensis and L. brasiliensis, respectively. It is concluded that the analyzed plants are promising as new and effective antiparasitic agents.